2020
DOI: 10.7196/samj.2020.v110i12.15296
|View full text |Cite
|
Sign up to set email alerts
|

The economics of poisoning: The role of telemedicine and toxicovigilance

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…All these studies were reported in 2020 during the COVID 19 outbreak. Two articles were cross‐sectional surveys (Armand et al, 2021 ; Feldman et al, 2021 ), one was a randomized controlled trial (Owolabi et al, 2020 ), one was a news article (Adebayo et al, 2020 ), one was a narrative review from Kenya (Jaguga & Kwobah, 2020 ), two were observational studies (Adebayo et al, 2021 ; Nlemadim et al, 2021 ), two were letters (Balme et al, 2020 ; Moolla et al, 2020 ), one was a commentary (Kamulegeya et al, 2020 ) and the other one was a retrospective and prospective analysis (Moyo & Madziyire, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these studies were reported in 2020 during the COVID 19 outbreak. Two articles were cross‐sectional surveys (Armand et al, 2021 ; Feldman et al, 2021 ), one was a randomized controlled trial (Owolabi et al, 2020 ), one was a news article (Adebayo et al, 2020 ), one was a narrative review from Kenya (Jaguga & Kwobah, 2020 ), two were observational studies (Adebayo et al, 2021 ; Nlemadim et al, 2021 ), two were letters (Balme et al, 2020 ; Moolla et al, 2020 ), one was a commentary (Kamulegeya et al, 2020 ) and the other one was a retrospective and prospective analysis (Moyo & Madziyire, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review showed the utilization of telemedicine in Zimbabwe, Cameroon, Uganda, South Africa, Nigeria, Mozambique, Tanzania, and Kenya. The most utilized mode of engaging patients was the telephones (P. Adebayo et al, 2020 ; Armand et al, 2021 ; Balme et al, 2020 ; Kamulegeya et al, 2020 ) and (Feldman et al, 2021 ). Two studies made use of the social media platform Whatsapp (Armand et al, 2021 ; Moyo & Madziyire, 2020 ) while some employed virtual platforms and video calls such as Skype (Armand et al, 2021 ; Moolla et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation